Postrevolutionary Iran the leader, the people, and the three powers - Asaadi, R. R. (Lexington Books, 2021)
"How have Iran's political institutions evolved since the revolution? This book is first a study of the structure of Iran's political institutions, of their composition and function in theory; and second an analysis of their evolution in practice over the first forty years of the Islamic Republic regime"--